Effect of carboxyl graphene nanofluid on automobile radiator performance. Issue 4 (20th April 2018) - Sumanth, S; Babu Rao, P; Krishna, V; Seetharam, TR; Seetharamu, KN
Abstract: Nanofluid is a promising solution for the improvement of the radiator performance. In the current research work, the effect of the nanofluid carboxyl graphene on the performance of a radiator is studied. Carboxyl graphene nanoplatelets are added to 50:50 ethylene glycol–distilled water at three concentrations of 0.02, 0.03, and 0.04 vol%. The liquid flow rate is varied from 3 liters per minute (LPM) to 6 LPM, and the inlet liquid to the radiator has been maintained at constant temperatures of 40 °C and 50 °C. The inlet air Reynolds number is varied between 1200 and 2500. The effects of these on performance parameters such as Nusselt number, effectiveness, and friction factor are investigated. It is observed that addition of carboxyl graphene nanoplatelets increases the Nusselt number and effectiveness of radiator while friction factor is unaltered. The effectiveness of radiator increases by 27.38% and 23.41% for inlet temperatures of 40 °C and 50 °C respectively at 0.02 vol% and 5 LPM flow rate.